The Effect of Intravenous Vitamin C on Cancer- and Chemotherapy-Related Fatigue and Quality of Life - Carr, Anitra C.; Vissers, Margreet C. M.; Cook, John S. (Frontiers in Oncology, 2014)
Cancer patients commonly experience a number of symptoms of disease progression and the side-effects of radiation therapy and adjuvant chemotherapy, which adversely impact on their quality of life (QOL). Fatigue is one of the most common and debilitating symptom reported by cancer patients and can affect QOL more than pain. Several recent studies have indicated that intravenous (IV) vitamin C alleviates a number of cancer- and chemotherapy-related symptoms, such as fatigue, insomnia, loss of appetite, nausea, and pain. Improvements in physical, role, cognitive, emotional, and social functioning, as well as an improvement in overall health, were also observed. In this mini review, we briefly cover the methods commonly used to assess health-related QOL in cancer patients, and describe the few recent studies examining the effects of IV vitamin C on cancer- and chemotherapy-related QOL. We discuss potential mechanisms that might explain an improvement in QOL and also considerations for future studies.